Answer:
maybe it's D ( not sure tho)
Answer:
When f(n) = 4n and g(n) = n² + 2n, f(g(-6)) = 96.
Step-by-step explanation:
To evaluate f(g(-6)), first find g(-6).
g(n) = n² + 2n
Substitute value.
g(-6) = (-6)² + 2(-6)
Square -6. Remember that (-x)² = x²
g(-6) = 36 + 2(-6)
Multiply 2 and -6.
g(-6) = 36 - 12
Subtract 12 from 36.
g(-6) = 24.
Now knowing this, substitute that value into f(n).
f(g(-6)) = f(24)
f(n) = 4n
Substitute value.
f(24) = 4(24)
Multiply 4 and 24.
f(24) = 96.
Answer:
See like terms have the same variables
E.g 2x+4y-x+7y
We should take the same variable together with the same signs so here
2x-x will be 1x
4y+7y will be 11 y
So x+11y
Hope it helps!
Just add it all together plus multiply